soln4

# soln4 - EE 562a Homework Solutions 4 26 February 2007 1 1...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: EE 562a Homework Solutions 4 26 February 2007 1 1. Solution: For each estimation problem you should draw the following block diagram and identify the desirable and observable quantities. Estimator Estimate Error Observable Desirable Model only For the linear estimator case we have the solution estimate = R (desirable)(observable) R- 1 observable observable (a) Use the notation r ( u ) = x ( u, 1) x ( u, 2) s ( u ) = x ( u, 3) x ( u, 4) , so that we view x ( u ) as a partitioned vector x ( u ) = r ( u ) s ( u ) which means we can also view the correlation matrix of x ( u ) as a partitioned matrix R x = R r R rs R sr R s . The desirable (quantity to be estimated) in this case is s ( u ) and the observable is r ( u ). Hence the desired estimator is ˆ s ( u ) = R sr R r- 1 r ( u ) . But since m x = , R x = K x = I = I O O I , the resulting estimate is ˆ s ( u ) = . This should not be too surprising because the components of x ( u ) are uncorrelated, so there is no second moment information in r ( u ) about s ( u ). (b) In this part, the desirable is y ( u ) and the observable is again r ( u ), so ˆ y ( u ) = R yr R r- 1 r ( u ) . 2 EE 562a Homework Solutions 4 26 February 2007 We must now get the cross-correlation term, so we partition G G = G r G s , where G r = 6 2 1 6 1 , G s = 3 2 3 6 2 1 6 . Then the desirable is y ( u ) = G r r ( u ) + G s s ( u ) , and the cross-correlation matrix is R yr = E { y ( u ) r † ( u ) } = E { G r r ( u ) r † ( u ) } + E { G s s ( u ) r † ( u ) } = G r R r + G s R sr = G r I + O = G r . The LMMSE estimate is then ˆ y ( u ) = G r r ( u ) = 6 2 1 6 1 x ( u, 1) x ( u, 2) . (c) First we write down the solution to the two estimation problems ˆ w ( u ) = R wv R- 1 v v ( u ) , ˆ z ( u ) = R zv R- 1 v v ( u ) . The only thing to do is find R zv . R zv = E { z ( u ) v † ( u ) } = E { Hw ( u ) v † ( u ) } = HR wv . So we have ˆ z ( u ) = HR wv R- 1 v v ( u ) = H ˆ w ( u ) . What happens if z ( u ) = g ( w ( u )), where g ( · ) is a nonlinear vector function? (d) The first thing to realize is that the result in (a) also gave us an estimate of x ( u ) based on the observation r ( u ): ˆ x ( u ) = r ( u ) , where we have used the simple fact the the best linear estimate of r ( u ) based on the observation r ( u ) is ˆ r ( u ) = r ( u )! Thus we identify x ( u ) ∼ w ( u ) , y ( u ) ∼ z ( u ) , r ( u ) ∼ v ( u ) , G ∼ H ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 7

soln4 - EE 562a Homework Solutions 4 26 February 2007 1 1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online